2004
DOI: 10.1002/ajmg.b.30056
|View full text |Cite
|
Sign up to set email alerts
|

Non‐replication of the brain‐derived neurotrophic factor (BDNF) association in bipolar affective disorder: A Belgian patient‐control study

Abstract: This patient-control association study was conducted to investigate a possible association of two single nucleotide polymorphisms (SNPs), g.11757C > G and g.196G > A, in the brain-derived neurotrophic factor (BDNF) with bipolar affective disorder (BPAD). Two hundred seventy-five individuals of Belgian origin (at least two generations of Belgian ancestors) were genotyped (112 BPAD and 163 controls). No significant differences were found in the frequency of genotypes and alleles of g.196G > A (P = 0.37 and 0.94,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 11 publications
(13 reference statements)
4
34
1
2
Order By: Relevance
“…For example, some studies used broad criteria in which individuals with MDD, bipolar disorders, and dysthymia were included, 41,[44][45][46][47] whereas others included individuals with MDD only. 11,33,35,42 There are two other issues in MDD that might contribute to the inconsistency of association findings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies used broad criteria in which individuals with MDD, bipolar disorders, and dysthymia were included, 41,[44][45][46][47] whereas others included individuals with MDD only. 11,33,35,42 There are two other issues in MDD that might contribute to the inconsistency of association findings.…”
Section: Introductionmentioning
confidence: 99%
“…31 In spite of this evidence, other investigators have not been able to replicate these findings in case-control association studies. [32][33][34][35][36][37][38] In the case of MDD, some studies reported a negative association of the Val66Met BDNF polymorphism, 33,39,40 while other studies have found a haplotype containing this variant to be positively associated to the MDD phenotype. 41,42 Moreover, positive associations of this single SNP and a haplotype containing it have been reported to be associated to childhood-onset mood disorder 41,43 as well as geriatric depression.…”
Section: Introductionmentioning
confidence: 99%
“…These include BDNF, which showed evidence for association with bipolar disorder in two cohorts of predominantly Caucasian origin, 15,16 although this has not been replicated in several other cohorts of European and Japanese origin. [17][18][19][20] Association and functional studies have also implicated the XBP1 gene in bipolar susceptibility, 21 but again, this has not been replicated in cohorts of European and Chinese origin. 22,23 Evidence has also been reported for association of the GRIN1 gene with bipolar disorder in a cohort of predominantly European Caucasian origin.…”
Section: Introductionmentioning
confidence: 99%